1996
DOI: 10.1002/j.1460-2075.1996.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Spc110p: assembly properties and role in the connection of nuclear microtubules to the yeast spindle pole body.

Abstract: Spc110p is an essential component of the budding yeast spindle pole body (SPB). It binds calmodulin and contains a long central coiled‐coil rod which acts as a spacer element between the central plaque of the SPB and the ends of the nuclear or spindle microtubules. This suggests that the essential function of Spc110p is to connect the nuclear microtubules to the SPB. To confirm this, we examined the phenotype of ts alleles of SPC110, one of which contains a mutation in the calmodulin binding site and was suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 41 publications
(56 reference statements)
4
88
0
1
Order By: Relevance
“…2). The nuclear receptor, Spc110 is a member of the pericentrin family of microtubule-nucleating proteins in which microtubule-nucleating motifs are separated from anchors by extended coiled-coil spacers (Kilmartin et al 1993;Kilmartin and Goh 1996;Sundberg and Davis 1997). These g-tubulin docking motifs are highly conserved from human pericentrin and kendrin through Drosophila centrosomin (CNN) to fission yeast Mto1 and Pcp1 (Flory et al 2002;Zhang and Megraw 2007;Fong et al 2008;Samejima et al 2008;Lin et al 2014).…”
Section: Structure and Duplication Cycle Of Yeast Spbsmentioning
confidence: 99%
“…2). The nuclear receptor, Spc110 is a member of the pericentrin family of microtubule-nucleating proteins in which microtubule-nucleating motifs are separated from anchors by extended coiled-coil spacers (Kilmartin et al 1993;Kilmartin and Goh 1996;Sundberg and Davis 1997). These g-tubulin docking motifs are highly conserved from human pericentrin and kendrin through Drosophila centrosomin (CNN) to fission yeast Mto1 and Pcp1 (Flory et al 2002;Zhang and Megraw 2007;Fong et al 2008;Samejima et al 2008;Lin et al 2014).…”
Section: Structure and Duplication Cycle Of Yeast Spbsmentioning
confidence: 99%
“…To date 27 proteins have been identified, and 18 have been localized to subregions of the spindle pole (Rout and Kilmartin, 1990;Spang et al, 1996;Sundberg et al, 1996;Wigge et al, 1998). A high percentage of these proteins have predicted coiled-coil domains, including Spc42p, which forms a central crystalline core (Donaldson and Kilmartin, 1996;Bullitt et al, 1997), and Spc110p, which acts as a molecular spacer between the central and inner plaques (Kilmartin et al, 1993;Kilmartin and Goh, 1996). The amino terminus of Spc110p in turn interacts with Spc98p Sundberg and Davis, 1997;Nguyen et al, 1998), which along with Spc97p (Knopp and Schiebel, 1997) and Tub4p (Sobel and Snyder, 1995;Marschall et al, 1996;Spang et al, 1996) make up the ␥-tubulin complex at the MT ends at both the inner and outer plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Spc98p, Spc97p, and Tub4p interact physically and functionally (Knop et al, 1997), and all three components localize to the inner and outer plaques (Rout and Kilmartin, 1990;Spang et al, 1996a;Knop et al, 1997). Spc110p is hypothesized to connect the ␥-tubulin complex in the inner plaque to the central plaque (Kilmartin and Goh, 1996). The carboxy terminus of Spc110p, which contains a calmodulin-binding site (amino acids 897-917) (Geiser et al, 1993;Stirling et al, 1994;Spang et al, 1996b), is located at the central plaque of the SPB .…”
Section: Introductionmentioning
confidence: 99%
“…The calmodulin-Spc110p interaction is required for proper chromosome segregation (Geiser et al, 1993;Kilmartin and Goh, 1996;Stirling et al, 1996;Sundberg et al, 1996). Characterization of the carboxy-terminal temperature-sensitive allele spc110 -220, which has a mutation in the calmodulin-binding site, revealed that calmodulin binding to Spc110p is required for the proper assembly of spindle pole components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation